Strategi Pengembangan Wakaf Produktif untuk Kesejahteraan Umat - Anisa Fitria Utami (Islam Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2019)
Abstract. The Strategy Of Productive Waqf Management For General Welfare (Case Study On Nadzir Of Malang Islamic University Foundation). The purpose of this research is to find out the strategy of productive waqf management for general welfare that conducted by The Nadzir of Universitas Islam Malang Foundation. Malang City still has a quite high poverty rate that is 4,6%. Waqf is an instrumen in islamic economy that can solve poverty beside zakat. The development of waqf in Malang City is increased every year plus there are many waqf asset that spreaded in all sub-district in Malang City. The Nadzir of Universitas Islam Malang Foundation that domiciled in Malang City was given funds by Kementrian Agama with waqf fund agreement. The purpose of that waqf fund is as the example on productive waqf management. The Nadzir of Universitas Islam Malang Foundation has succeed in developing eleven VIP Rooms in UNISMA Hospital. 70% from the outcomes of that management, are used to development and management of the VIP Rooms and used to develop a minimarket that spreaded in several regions. 20% from the outcomes of productive waqf management was channeled to the 40 mauquf alaih periodically.